The Role of Hysteroscopy in Endometrial Hyperplasia - Wachyu Hadisaputra (Indonesian Socety of Obstetrics and Gynecology, 2011)
Objective: To review, presented the role of hysteroscopy in endometrial hyperplasia. Method: Literatur review. Conclusion: The high diagnostic accuracy, associated with a minimal trauma, renders hysteroscopy the ideal procedure for both diagnosis and follow up of conservative management of endometrial hyperplasia. Hysteroscopy has made the most significant progress, mainly because the ability to use fine diameter instruments makes it feasible to avoid both anaesthesia and cervical dilatation. The procedure may therefore be performed in an outpatient setting without the need for hospitalization. The hysteroscopic diagnosis should not replace histological diagnosis, mostly in hysteroscopies performed after progestagen therapy, because the changes induced by drugs make more difficult the interpretation of hysteroscopy. The hysteroscopic pattern of endometrial hyperplasia appears with an over development of the endometrial mucosa with increased glandular openings, increased vascularization, cystic dilatations, polypoid aspects. Innovations in the diagnostic aspect of serious endometrial diseases through hysteroscopy is still evolving. [Indones J Obstet Gynecol 2011; 35-2: 91-4] Keywords: hysteroscopy, endometrial hyperplasia